THE DEVELOPMENT OF ENGLISH COMMUNICATION SKILLS WITH LEARNING MANAGEMENT LANGUAGE TEACHING COMMUNICATION JOIN TO MULTIMEDIA FOR PRATHOMSUKSA 4 STUDENTS - Thong-ek, Supapich; Thaweboon, Samorn (Journal for Developing the Social and Community, 2023)
The purposes of this research were 1) to develop effective English communication skills management according to the 70/70 criteria 2) to compare communication skills in English listening according to the 70% criteria 3) to compare communication skills. 70% English speaking 4) to compare the English language learning achievement before and after studying of 4th grade students with language learning management for communication with mixed media. The target groups used in the research were Grade 4 students, Ban Tha Ladwaree Witthaya School, second semester of the academic year 2020, consisted of 13 students, 8-week experiment period. The research instruments consisted of 1) learning management plan 2) learning achievement test 3) Communication, Listening-Speaking Skills Assessment Form The statistics used in the data analysis were mean, percentage and standard deviation. The instruments were used in the experiment including 1) learning management plan 2) learning management plan assessment form 3) evaluation test Learning achievement 4) Listening assessment form 5) Speaking assessment form the used statistics in data analysis were mean, percentage and standard deviation The results of research showed that 1) The efficiency of language learning management for communication with mixed media to improve the learning management of English communication skills of grade 4 students with an efficiency of 79.38/81.54, which is higher than the set criteria of 70/70. 2)English listening communication skills scores of grade 4 students by learning management language for communication with mixed media with an average score of 84.62%, which is 70 percent higher than the specified threshold. 3) English speaking communication skills scores of grade 4 students by learning management language for communication with mixed media with an average score of 78.46 percent, which is 70 percent higher than the specified threshold 4) English language achievement scores of 4th grade students by organizing language learning for communication with mixed media After studying, it was significantly higher than before at the .05 level.